Exploring the feasibility and clinical impact of ultrasound microvascular flow imaging in detecting brain injury in hyperbilirubinemia neonates - Shuang He; Meiyu Wang; Man Zhu; Min Zhang; Xueni He; Xiang Jiang; Shu Tang; Zhaoxia Wang (Scientific Reports)
Abstract Neonatal hyperbilirubinemia is a prevalent condition during the neonatal period, and in severe instances, it can result in brain damage accompanied by irreversible neurological consequences. Therefore, early detection and intervention are paramount. This research aimed to detect early-stage brain damage resulting from neonatal hyperbilirubinemia through the application of two-dimensional cranial ultrasound and microvascular blood flow (MV-Flow) imaging techniques. Clinical data, along with gray-scale and microvascular ultrasound images of the basal ganglia, were collected from 85 neonates (hyperbilirubinemia group vs. non-hyperbilirubinemia group: 51 vs. 34). The Globus Pallidus to Putamen (G/P) ratio and the vascular index (VIMV) were calculated. A comparative analysis of clinical and ultrasonographic data between the groups was conducted. The hyperbilirubinemia group had higher mean G/P ratios (1.39 ± 0.49 vs. 1.16 ± 0.12, P < 0.05) and lower VIMV, which was negatively correlated with TSB levels (coronal: r = -0.419, P < 0.05; parasagittal: r = -0.448, P < 0.05). Cranial gray-scale ultrasound demonstrates altered gray values in the basal ganglia region, and the MV-Flow technique reveals and quantifies the microvascular structure of this region. These methods may serve as potential biological markers for the early assessment of bilirubin-induced brain damage.